2000
DOI: 10.1007/s005350050021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of n-3 fatty acid-rich diet and nutritional education for the maintenance of remission in Crohn's disease

Abstract: Elemental diet (ED) therapy has been established as primary therapy for Crohn's disease, and home enteral nutrition (HEN) has been reported to control relapse at a dose of more than 30kcal/kg of ideal body weight. However, a decrease in ED compliance with long-term use is becoming problem. We developed an n-3 fatty acid-rich diet and carried out nutritional education specifically for Crohn's disease patients using HEN to facilitate compliance and to improve their nutritional status. After the introduction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…69,70 Other approaches have been unconvincing, particularly interventions specifically with n-3 PUFAs, 71 but such studies have uncertain rele vance to the use of diets high in n-3 PUFA-rich foods, which have their advocates, alas without high-quality evidence of benefit. 72 Reducing microparticle intake was unsuccessful in l owering r emission rates over 4 months in a well-powered RCT. 73 One disease that might represent a phenotype of Crohn's disease is orofacial granulomatosis.…”
Section: Ulcerative Colitismentioning
confidence: 99%
“…69,70 Other approaches have been unconvincing, particularly interventions specifically with n-3 PUFAs, 71 but such studies have uncertain rele vance to the use of diets high in n-3 PUFA-rich foods, which have their advocates, alas without high-quality evidence of benefit. 72 Reducing microparticle intake was unsuccessful in l owering r emission rates over 4 months in a well-powered RCT. 73 One disease that might represent a phenotype of Crohn's disease is orofacial granulomatosis.…”
Section: Ulcerative Colitismentioning
confidence: 99%
“…On the other hand, eicosanoids such as leukotriene B4 (LTB4) and thromboxane A2 (TXA2) are produced in the arachidonic acids cascade by n-6 fatty acids, which are a group of polyvalent unsaturated fatty acids. LTB4 and TXA2 are assumed to be the inflammatory substances that cause Crohn's disease [12,13]. LTB4 acts as the inflammatory mediator, which induces the liberation and adhesion of leukocyte, and TXA2 coagulates the platelet, and constricts the blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…N-3 fatty acids competitively inhibit the metabolism of n-6 fatty acids and have a close affinity to the rate-limiting enzymes. LTB5, TXA3 and other n-3 fatty acid metabolites are synthesized with a higher priority to cause anti-inflammatory activity [2,12]. Accordingly, for Crohn's disease, the ratio of n-6/n-3 is more important than the amount of fat in the enteral nutrient formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of CD with supplemental fish oil has been demonstrated to reduce the occurrence of relapse. Tsuijikawa and coworkers 14 suggest that the n-3 polyunsaturated fatty acids, taken up in competition with n-6 polyunsaturated fatty acids, decrease the induction of inflammatory eicosanoids such as leukotriene B4 and control inflammation. Others found that supplementation with omega-3 fatty acids delayed relapse.…”
Section: In Youthmentioning
confidence: 98%